„Patrzcie, oto jest film produkcji polskiej”. Przedwojenna polska komedia muzyczna jako musical - Nowińska, Małgorzata (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article, “Look, here is a Polish film production.” Pre-war Polish musical comedy as a musical, is an attempt to prove that Polish musical comedies from the 1930s can be recognized as a local version of a classic film musical. Based on an analysis of two representative films from this period, Piętro wyżej (L. Trystan, 1937) and Zapomniana melodia (J. Fethke, K. Tom, 1938), the author proves that these productions are in line with the definition and determinants of the American genre. The historical context invoked allows the author to better describe the musical’s Polish variant and how it differs from the original. The article cites press reviews from the 1930s, based on which the author describes the evolving approach of critics and audiences to the changes in music present in these films as a result of drawing on American works. Finally, the article focuses on the importance of interwar musical comedies in Polish culture.